Volitional components of consciousness vary across wakefulness, dreaming and lucid dreaming - Dresler, Martin; Eibl, Leandra; Fischer, Christian F.; Wehrle, Renate; Spoormaker, Victor I.; Steiger, Axel; Czisch, Michael; Pawlowski, Marcel (Frontiers in Psychology, 2014)
Consciousness is a multifaceted concept; its different aspects vary across species, vigilance states or health conditions. While basal aspects of consciousness like perceptions and emotions are present in many states and species, higher-order aspects like reflective or volitional capabilities seem to be most pronounced in awake humans. Here we assess the experience of volition across different states of consciousness: 10 frequent lucid dreamers rated different aspects of volition according to the Volitional Components Questionnaire for phases of normal dreaming, lucid dreaming and wakefulness. Overall, experienced volition was comparable for lucid dreaming and wakefulness, and rated significantly higher for both states compared to non-lucid dreaming. However, three subscales showed specific differences across states of consciousness: planning ability was most pronounced during wakefulness, intention enactment most pronounced during lucid dreaming, and self-determination most pronounced during both wakefulness and lucid dreaming. Our data confirm the multifaceted nature of consciousness: different higher-order aspects of consciousness are differentially expressed across different conscious states.